2021
DOI: 10.3389/fenvs.2021.704097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water and Nitrogen Addition on the Seed Yield and Germination Characteristics of the Perennial Grass Leymus chinensis (Trin.) Tzvel

Abstract: The reproductive characteristics of plants are likely affected by climate change e.g., changes in precipitation patterns and nitrogen deposition, but few studies have examined the effects of these ecological agents of selection on the seed yield and germination characteristics of perennial grasses. Here, we conducted a multiple-year pot experiment with Leymus chinensis, a common perennial grass in the eastern region of the Eurasian steppe zone, which was grown under three water treatments with and without nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Plastic pots (diameter and height, 30 cm) were filled with 10 kg of sieved soil that had a pH of 7.12, electrical conductivity of 0.73 dS/m, and concentrations of soil organic carbon, nitrogen, and phosphorus at 2.83%, 1.37 g/kg, and 0.67 g/kg, respectively [ 44 ]. L. chinensis ‘Dongdi 4’ seedlings of uniform size without offspring ramets were excavated to a depth of 15 cm from the same field site (Figure S1 ) and transplanted into the plastic pots on 15 May 2016, 15 May 2017, and 15 May 2018 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plastic pots (diameter and height, 30 cm) were filled with 10 kg of sieved soil that had a pH of 7.12, electrical conductivity of 0.73 dS/m, and concentrations of soil organic carbon, nitrogen, and phosphorus at 2.83%, 1.37 g/kg, and 0.67 g/kg, respectively [ 44 ]. L. chinensis ‘Dongdi 4’ seedlings of uniform size without offspring ramets were excavated to a depth of 15 cm from the same field site (Figure S1 ) and transplanted into the plastic pots on 15 May 2016, 15 May 2017, and 15 May 2018 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All plants were grown in the field beneath a transparent polyvinylchloride roof. Belowground irrigation was applied once every two days at 193 ml·pot − 1 , which was calculated on the basis of 498 mm mean annual precipitation [ 44 ]. Concentrations of N, P, and K in the irrigation water were below the limits of detection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive and significant correlation was observed between seed vigor and radicle length and caulicle length, which is because these two traits are part of seed vigor (Table 5). Some previous studies have shown a decrease in seed germination produced by the mother plant under nitrogen application conditions (Zhao et al, 2021), and some other studies have indicated an increase in seed germination produced by the mother plant under nitrogen application conditions (Oskouie, 2012).…”
Section: Laboratory Experimentsmentioning
confidence: 96%
“…For all experiments, 25 seeds were placed in each Petri dish, and each treatment was repeated four times. Petri dishes were kept in an incubator (Harbin, China) at 16/28 • C with a 12/12 h dark/light diurnal cycle [47,53]. Germination was checked once a day, and the experiment was stopped when no germination was observed for three consecutive days.…”
Section: Germination Experimentsmentioning
confidence: 99%